Corporate Social Responsibility, Emirates Airlines and Reliance Industries Ltd – A Study - Rammohan Sundaram , (International Journal of Advanced Science and Technology, 2020)
This is an attempt by the scholar to showcase the excellent initiatives of Emirates Airlines Foundation, which has several initiatives in CSR and the most noteworthy was the Emirates Lifeline Express in India, which is Hospital on Rails in India, which caters to the under privilege of the country from Kashmir to Kanyakumari, the second one he had written about was the Emirates Ship, which went to remote parts of Bangladesh by sea and lakes to serve the socially challenged public of Bangladesh and finally was the efforts in Uganda in partnership with a US NGO helping the poor from education to health ensuring they contributed responsibly to the society through their The scholar is now highlighting the efficiency of the company through its foundation on how they are serving the destitute street children in Chennai who are affected by the deadly HIV Virus, which has the necessary blessings from the government (Thiel, M. 2015).